A Study on Users’ Adoption of Electronic Payment System in India. - M. Chandrasekaran, Ghana Shyam Kafley, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The traditional payment system has got its own limitation to adopt recent developments in the commercial world. The growth of Electronic payment systems is inevitable in the Indian industrial and business scenario. Digital India movement of Indian Government also focuses move towards E-Payment systems. Technology has immense contribution to the growth and development of the banking sector. There have been massive changes in the concept of banking after the digitalization of India's banking sector. Commercial banks in India are facilitating their customers to develop a convenient platform for E- Payment system. In this present study, the researcher studied the relationship between the seven factors technological factors, security, Trust, social influence, internet connectivity, Perceived ease of use, Perceived Usefulness, and Intention to use to measure the adoption of e-payment systems in Madurai district. The study results show that Trust, Perceived Usefulness, and perceived ease of use are statistically significant, indicating that this variable has a positive effect on Intention to use e-payment.